(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This research aimed to uncover the truth of the thought of the unknown Syrian philosopher Bardesanal-Rahawi, in the face of the unscientific readings that gave an inaccurate picture of him. This revelation was based on an attempt to show that Bardesan had a deep philosophical vision that emerged in raising the problem of freedom of human will and finding solutions in relation to the position and function of man in the world.In addition to analyzing Bardesan’s opinion on the changing nature of human being and showing Bardesan’s rejection of any constant human essence that imposes its presence on man, it prevents him from moving towards initiative and reconfiguring his reality. On this basis, Bardesan was able to show that man exists naturally and that nature tries to reach this human being to its utmost perfection. However, Bardesan emphasized the role of freedom of human will in the face of predestination, in order that Bardesan tried to prove the centrality of man in the universe and his ability to control his human destiny to the possible maximum extent.